1995
DOI: 10.1021/jm00021a022
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Taste Correlations in Sweet Dihydrochalcone, Sweet Dihydroisocoumarin, and Bitter Flavone Compounds

Abstract: The dihydrochalcone derivatives of the bitter flavonoids naringin and neohesperedin are intensely sweet. Phyllodulcin is as sweet as the dihydrochalcones with similar taste properties although its structure apparently resembles that of bitter flavanone or flavone. Multifaceted approaches, including X-ray crystal structure analysis, energy calculation, and structure comparison, have been employed to clarify the structure-taste correlations in these classes of compounds. In the crystal, naringin dihydrochalcone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…1). The corresponding bond lengths and angles of these two molecules agree with each other and show normal values (Allen et al, 1987), and are comparable to those observed in the other monoclinic polymorph (De Matheus et al, 1991) and a closely related structure (Shin et al, 1998(Shin et al, or 1995.…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…1). The corresponding bond lengths and angles of these two molecules agree with each other and show normal values (Allen et al, 1987), and are comparable to those observed in the other monoclinic polymorph (De Matheus et al, 1991) and a closely related structure (Shin et al, 1998(Shin et al, or 1995.…”
Section: Figuresupporting
confidence: 84%
“…The title compound, (I), was isolated from the leaves of R. siamensis, which were collected from Songkhla province in the southern part of Thailand. The naringin dihydrochalcone, which is a derivative of compound (I), was known as a sweetener (Shin et al, 1998(Shin et al, or 1995. As part of our systematic studies on chemical constituents of Thai medicinal plants (Chantrapromma et al, 2003(Chantrapromma et al, , 2004(Chantrapromma et al, , 2005Boonnak et al, 2005;Thongdeeying et al, 2005;Fun et al, 2005), we have undertaken the X-ray crystal structure analysis of (I) in order to establish its molecular structure and relative stereochemistry.…”
Section: Figurementioning
confidence: 99%
“…Total flavonoids only showed a significant and moderate relationship with acid taste. Most of the literature related flavonoids with bitter, acid or astringent tastes [25] but minor alterations in the flavonol structure can change their taste from bitter to sweet or the other way around [26].…”
Section: Turnip Greensmentioning
confidence: 99%
“…Die Süßempfindung wird durch eine bestimmte räumliche Anordnung des Moleküls ausgelöst, für die es passende Geschmacksrezeptoren auf der Zunge gibt. Neohesperidin DC hat die Form eines »J«, wobei der Dihydrochalkon-Teil des Moleküls nur zum Teil ausgestreckt vorliegt (25).…”
Section: Süßempfindung Und Strukturunclassified